Geología de la Ventania (Provincia de Buenos Aires, Argentina) - Sellés Martínez, José (Journal of Iberian Geology, 2001)
The geologic province of Ventania, in the south-west of the Province of Buenos Aires (Republica Argentina) is the most important outcrop on the South American Dpto. de Ciencias Geológicas, Facultad de Ciencias Exactas y Naturales, Universidad de Buenos Aires. * Email: pepe@gl.fcen.uba.ar. 43 José Sellés-Martínez Plate of what formerly was a continuous basin fringing the south-western margin of Gondwana during Palaeozoic times. This part of the basin, along with what at present are the South African, Australian and Antarctic counterparts, was deformed in the Permo-Triassic to become the Gondwanides. In Ventania area, the basin was receptive from Lower to Upper Palaeozoic, and was deformed in a single episode under moderate pressure and temperature, actually about 400 C° y 23Kb. The most outstanding feature is the folding, at different scales, decreasing in intensity from SW to NE. The sigmoidal shape of the belt -and many of the micro- and mesostructures present- are the result of penetrative simple shear deformation acting on the horizontal plane. The SW tilting of axial planes of regional folds is assigned to vertical shear directed top to NE.